Tiroidite pós-parto. - Fernando Rodrigues (Acta Médica Portuguesa, 2003)
The author refers to the main clinical symptoms, diagnosis, treatment and evaluation of the post-partum thyroiditis. Researches can reveal different post-partum thyroiditis, considering the diagnosis and screening. Normally the classical presentation of post-partum thyroiditis includes a period of thyrotoxicosis, followed by hypothyroidism and finally thyroid functions in its normal levels. According to some statistic investigation, authors mention that after a period of normal and stable status, hypothyroidism can prevail as a long-term disease.